Meningitis in a Canadian Adult due to High Level Penicillin-Resistant, Cefotaxime-Intermediate Streptococcus pneumoniae - Cécile Tremblay; Anne-Marie Bourgault; Pierre St-Antoine (Canadian Journal of Infectious Diseases)
Invasive penicillin-resistant pneumococcal (PRSP) infections are increasing worldwide. In Canada, the incidence of penicillin resistance among Streptococcus pneumoniae isolates is estimated at greater than 6%. In Quebec, only one case of PRSP meningitis has been reported and involved an infant. An adult patient is described who presented with meningitis caused by high level penicillin-resistant, cefotaxime-intermediate S pneumoniae.